Oral Glucosamine Effect on Blood Glucose and Insulin Levels in Patients With Non-Diabetic Osteoarthritis: A Double-Blind, Placebo-Controlled Clinical Trial - Massoud SAGHAFI,; Marjaneh KARIMI,; Shokoufeh BONAKDARAN,; Nadia MASSOUDNIA, (Archives of Rheumatology, 2016)
Objectives: This study aims to determine the effects of oral glucosamine on glucose metabolism and insulin resistance in non-diabetic patients with osteoarthritis in Northeastern Iran. Patients and methods: This placebo-controlled, randomized clinical trial included 40 non-diabetic patients with osteoarthritis (15 males, 25 females, mean age 63.8±7.64 years; range 49 to 80 years). Patients were randomly divided into two equal groups and treated with oral glucosamine sulfate 1500 mg a day or placebo for 90 days. Fasting blood sugar, glucose tolerance test with 75 grams glucose and serum insulin levels, and homeostatic model assessment-insulin resistance were evaluated initially and at the end of intervention. Results: There were no significant differences between the groups in terms of blood sugar, glucose tolerance test, and insulin levels at the beginning and end of the study. In the oral glucosamine group, there were no significant changes in fasting blood sugar (94.1±7.14 mg/dL versus 93.5±9.45 mg/dL, p=0.15), glucose tolerance test (99.3±8.99 mg/dL versus 103.3±10.1 mg/dL, p=0.07), and homeostatic model assessment-insulin resistance (1.57±0.21 versus 1.48±0.21, p=0.13) after treatment. Also, placebo did not significantly affect serum glucose levels and insulin resistance. Conclusion: Oral glucosamine with routine dosage was safe in our non-diabetic patients with osteoarthritis and had no significant effect on glucose metabolism and insulin resistance.